Comparative Studies of Vertebrate Beta Integrin Genes and Proteins: Ancient Genes in Vertebrate Evolution - Ujjwal K. Rout; Roger S. Holmes (Biomolecules, 2011)
Intregins are heterodimeric α- and β-subunit containing membrane receptor proteins which serve various cell adhesion roles in tissue repair, hemostasis, immune response, embryogenesis and metastasis. At least 18 α- (ITA or ITGA) and 8 β-integrin subunits (ITB or ITGB) are encoded on mammalian genomes. Comparative ITB amino acid sequences and protein structures and ITB gene locations were examined using data from several vertebrate genome projects. Vertebrate ITB genes usually contained 13–16 coding exons and encoded protein subunits with ~800 amino acids, whereas vertebrate ITB4 genes contained 36-39 coding exons and encoded larger proteins with ~1800 amino acids. The ITB sequences exhibited several conserved domains including signal peptide, extracellular β-integrin, β-tail domain and integrin β-cytoplasmic domains. Sequence alignments of the integrin β-cytoplasmic domains revealed highly conserved regions possibly for performing essential functions and its maintenance during vertebrate evolution. With the exception of the human ITB8 sequence, the other ITB sequences shared a predicted 19 residue α-helix for this region. Potential sites for regulating human ITB gene expression were identified which included CpG islands, transcription factor binding sites and microRNA binding sites within the 3’-UTR of human ITB genes. Phylogenetic analyses examined the relationships of vertebrate beta-integrin genes which were consistent with four major groups: 1: ITB1, ITB2, ITB7; 2: ITB3, ITB5, ITB6; 3: ITB4; and 4: ITB8 and a common evolutionary origin from an ancestral gene, prior to the appearance of fish during vertebrate evolution. The phylogenetic analyses revealed that ITB4 is the most likely primordial form of the vertebrate β integrin subunit encoding genes, that is the only β subunit expressed as a constituent of the sole integrin receptor ‘α6β4’ in the hemidesmosomes of unicellular organisms.